(untitled) (Marketing Journal, 2025)
This article discusses the development of logistics services in material flow management in manufacturing enterprises, including methods of delivering material resources used in the production process, “pushing” and “pulling” methods, specific aspects of t heir use in material flow management in manufacturing enterprises, and inter-departmental movement of material resources in manufacturing enterprises.